Feeding and Swallowing Characteristics of Children With Esophageal Atresia and Tracheoesophageal Fistula. Issue 3 (28th December 2022) - Maybee, Jennifer; Deck, Jacklyn; Jensen, Emily; Ruiz, Amanda; Kinder, Sarah; DeBoer, Emily
Abstract : Objectives: This study aimed to characterize feeding/swallowing difficulties in children with esophageal atresia and/or tracheoesophageal fistula (EA/TEF) and evaluate associations among feeding difficulties, pharyngeal dysphagia (PD), and other aerodigestive evaluation findings. Methods: This was a retrospective cohort study of feeding/swallowing characteristics of 44 patients with EA/TEF treated in the aerodigestive program of a single academic medical institution from 2010 to 2015. Demographics, comorbidities, presence and characteristics of feeding/swallowing difficulties, and results of relevant diagnostic tests [videofluoroscopic swallow studies (VFSS), clinical feeding evaluations (CFEs), chest computerized tomography (CT) scans, pulmonary bronchoscopies, and upper GI (UGI)/esophagrams] were reviewed. Results: Fifty percent of the cohort had PD and 88.6% had feeding difficulties. Across 118 encounters (87 VFSS and 31 CFEs), feeding difficulties suggestive of esophageal dysphagia were most frequently seen in children over 48 months and feeding difficulties suggestive of developmental feeding problems were most frequently seen in children from 24 to 48 months. Abnormal findings were present in 59.8% of VFSS, with aspiration (34.5%) and pharyngeal residue (26.4%) the most frequently observed signs of dysphagia. Abnormal UGI/esophagram findings were not associated with significantly increased risk of feeding difficulties during visits within 3 months (risk ratio, RR = 1.33). Presence of dysphagia was associated with increased risk for some abnormal CT findings (RR= 3.0 for airspace and 3.0 for bronchiectasis). Conclusions: Feeding/swallowing difficulties are common in EA/TEF, and types of feeding difficulties vary by patient age. The presence of abnormal findings on UGI/esophagram did not increase the risk of feeding complaints; however, the presence of dysphagia increased the risk of abnormal chest CT.